Frequency of Dementia in Type II Diabetes Mellitus - Sajid Iqbal, Afshan Gul, Sahar Farhat, Najma Fida, Asma Mehmood, Sara Noreen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus is the most prevailing non- communicable diseases worldwide. It is the main reason of morbidity and mortality. Cognitive dysfunction is one of the major complications associated with diabetes. It is a risk factor for cognitive decline as the duration of diabetes progress and if accompanied by hypoglycemic attacks. Aim: To determine the frequency of dementia in patients suffering from type II diabetes mellitus. Study design: Descriptive cross-sectional study Place and duration of study: Medical Department, Khyber Teaching Hospital, Peshawar from 1st March 2019 to 30th September 2019 Methodology: Two hundred and thirty five male and female patients suffering from diabetes mellitus from past 2 years were enrolled. The subjects were clinically assessed through history and physical examination. Results: The mean age was 60±10.26 years with 42% male patients and 58% female patients. 12% of patients had dementia where as in 88% of patients it was not observed. Conclusion: The frequency of dementia in patients suffering from type II diabetes mellitus is 12%. Key words: Diabetes, Dementia, Hypoglycemia